Clinical Manifestations of Lumbar Osteochondrosis and Stenozis of the Lumbar Spinal Canal - Botirov, N. T.; Mamadzhanov, K. Kh.; Isakov, B. M.; Abdulazizov, O. N.; Jalilov, F. R. (European Journal of Life Safety and Stability (2660-9630), 2022)
Spinal stenosis as the leading cause of vertebrogenic neurological disorders remains poorly understood. Mostly there are works devoted to the diagnosis and treatment of cervical vertebrogenic myelopathy caused by a narrow spinal canal. Some clinicians and practitioners pay attention to stenosis of the lumbar spinal canal (1-3). Most aspects of this problem are not well understood.